Large retroperitoneal mass in a 56-year old female - Nuhi Arslani (Acta Medico-Biotechnica, 2021)
Purpose: Müllerian ductal cysts are rare congenital abnormalities of Müllerian system regression, typically located in the pelvis . Their presence in retroperitoneum is extremely rare, as the incidence of retroperitoneal cysts, even of diverse morphology and etiology, is approximately 1 in 100,000 adult admissions. Moreover, they can be classified into lymphatic, mesothelial, enteric, and urogenital cysts. Urogenital cysts are further categorized into pronephric, mesonephric, metanephric, and Müllerian types. However, in both sexes the most common location of the Müllerian cyst is in the pelvis; in men they reside mostly near the prostatic utricle and the appendix of the testis. In women, they may be often confused with primary ovarian or tubal cysts.Case Report: In this case report, we present a case of a benign retroperitoneal cyst of the Müllerian type in a 56- year old female.